2022
DOI: 10.1021/acs.est.2c03919
|View full text |Cite
|
Sign up to set email alerts
|

A Carotenoid- and Nuclease-Producing Bacterium Can Mitigate Enterococcus faecalis Transformation by Antibiotic Resistance Genes

Abstract: Dissemination of antibiotic resistance genes (ARGs) through natural transformation is facilitated by factors that stabilize extracellular DNA (eDNA) and that induce reactive oxygen species (ROS) that permeabilize receptor cells and upregulate transformation competence genes. In this study, we demonstrate that Deinococcus radiodurans can mitigate this ARG dissemination pathway by removing both eDNA and ROS that make recipient cells more vulnerable to transformation. We used plasmid RP4 as source of extracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 79 publications
(125 reference statements)
0
4
0
Order By: Relevance
“…radiodurans cannot interfere with the functional evolution of indigenous microbial communities. Moreover, the products of eDNA biodegradation may also mitigate the spread of ARGs among bacteria by decreasing oxidative stress. ,, It has been reported that an eDNA product, deoxyguanosine monophosphate (dGMP), can act as a nutrient source for bacteria and enhance bacteria tolerance to oxidative stress, which makes bacteria more vulnerable to acquire ARG by HGT . Therefore, the synthetic microbiome may also reduce the risk of ARG spread by changing the microbial community and degrading eDNA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…radiodurans cannot interfere with the functional evolution of indigenous microbial communities. Moreover, the products of eDNA biodegradation may also mitigate the spread of ARGs among bacteria by decreasing oxidative stress. ,, It has been reported that an eDNA product, deoxyguanosine monophosphate (dGMP), can act as a nutrient source for bacteria and enhance bacteria tolerance to oxidative stress, which makes bacteria more vulnerable to acquire ARG by HGT . Therefore, the synthetic microbiome may also reduce the risk of ARG spread by changing the microbial community and degrading eDNA.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we demonstrated that the nucleaseproducing Deinococcus could mitigate transformation of extracellular ARGs to Enterococcus faecalis by degrading eDNA. 18,19 Therefore, this study mainly demonstrates whether these nuclease-producing bacteria can reduce the risk of ARG dissemination in mixed bacteria sewage systems. In this study, a microbiome capable of degrading eDNA was constructed and operated by using Deinococcus radiodurans as the base microorganism.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the present study only analyzed the number of enzymes related to the purine salvage pathway without further analyzing the specific mechanism. Therefore, we cannot yet fully explain why Enterococcus survived antibiotic treatment, suggesting that the antibiotic resistance genes of bacteria are non-negligible factors for antibiotic susceptibility and not just due to the purine salvage pathway alone ( Enterococcus are known to be resistant to ampicillin, and their resistance mechanisms have been clearly described) [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, it is considered that microbes dominate the degradation process, including direct degradation through nucleases and indirectly mediated ARG attenuation. For example, Deinococcus radiodurans and Bdellovibrio bacteriovorus HD are crucial in ARG biodegradation as they produce nucleases. Multicellular organisms, such as earthworms, , Musca domestica larvae, and Hermetia illucens, can also mediate ARG biodegradation by affecting the microbial communities.…”
Section: Introductionmentioning
confidence: 99%